2014
DOI: 10.1111/1574-6968.12461
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the defence-related mechanism in cucumber seedlings in relation to root colonization by nonpathogenicFusarium oxysporumCS-20

Abstract: A defence response can be induced by nonpathogenic Fusarium oxysporum CS-20 in several crops, but the molecular mechanism has not been clearly demonstrated. In the present study, we analysed the defence mechanism of a susceptible cucumber cultivar (Cucumis sativus L. 9930) against a pathogen (F. oxysporum f. sp. cucumerinum) through the root precolonization of CS-20. A challenge inoculation assay indicated that the disease severity index (DSI) was reduced, ranging from 18.83 to 61.67 in comparison with the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 48 publications
3
30
0
Order By: Relevance
“…JA is known to play major roles in the regulation of the plant immune system. Pathogen-induced LOX transcript accumulation has been reported in cucumber after inoculation with F. oxysporum CS-20 [45]. Although, this interaction is not the same, we found a similar pattern in our experiment, in which LOX1 showed activation after inoculation with P. melonis.…”
Section: Rt-qpcr Analysis Of Gene Expressionsupporting
confidence: 86%
“…JA is known to play major roles in the regulation of the plant immune system. Pathogen-induced LOX transcript accumulation has been reported in cucumber after inoculation with F. oxysporum CS-20 [45]. Although, this interaction is not the same, we found a similar pattern in our experiment, in which LOX1 showed activation after inoculation with P. melonis.…”
Section: Rt-qpcr Analysis Of Gene Expressionsupporting
confidence: 86%
“…In contrast, in cucumber roots CS-20 did induce major transcriptional changes, and at 72 hpi there was a strong induction of PR3, LOX1, PAL1, and NPR1 and of CaMs, CsCam7 and CsCam12 being the strongest induced. At the same time point pathogenic Foc induced NPR1 and to a lesser extent PR3 and PAL1 expression (Pu et al, 2014). RNA-seq analysis of soybean roots inoculated with endophytic or pathogenic Fo revealed that the latter induced more, and stronger, transcriptional changes at 72 and 96 hpi (Lanubile et al, 2015).…”
Section: De Lamo and Takkenmentioning
confidence: 91%
“…This difference indicates that even at later stages of root colonization Fo47 does not reach the vasculature. Contrarily, Fo47 was reported to colonize xylem vessels of eucalyptus (Salerno et al, 2000) and the Fo endophyte CS-20 was found to colonize xylem vessels of cucumber (Pu et al, 2014). An explanation for the vascular presence of the latter two endophytic strains could be the clipping of the roots prior to inoculation, providing direct vascular access to the endophyte.…”
Section: Host Colonizationmentioning
confidence: 99%
See 2 more Smart Citations